Challenges in Testing of Web Applications (International Journal of Engineering and Computer Science, 2017)
Testing is one of the most important phase in software development life cycle. It actually plays a very important role in the software product success by improving its quality. There are so many challenges of testing are involved in Web-based applications. But interoperability and integration are the most important testing challenges that are associated with Web-based applications. Now a day’s Web-based applications importance and complexity is also increasing and they are evolving and emerging rapidly. This paper introduces the Integration and Interoperability issues of Web-based Applications.